Viral indicators for tracking domestic wastewater contamination in the aquatic environment - Farkas, Kata; Walker, David I.; Adriaenssens, Evelien M.; McDonald, James E.; Hillary, Luke S.; Malham, Shelagh K.; Jones, Davey L. (Water research (Oxford), 2020)
Waterborne enteric viruses are an emerging cause of disease outbreaks and represent a major threat to global public health. Enteric viruses may originate from human wastewater and can undergo rapid transport through aquatic environments with minimal decay. Surveillance and source apportionment of enteric viruses in environmental waters is therefore essential for accurate risk management. However, individual monitoring of the >100 enteric viral strains that have been identified as aquatic contaminants is unfeasible. Instead, viral indicators are often used for quantitative assessments of wastewater contamination, viral decay and transport in water. An ideal indicator for tracking wastewater contamination should be (i) easy to detect and quantify, (ii) source-specific, (iii) resistant to wastewater treatment processes, and (iv) persistent in the aquatic environment, with similar behaviour to viral pathogens. Here, we conducted a comprehensive review of 127 peer-reviewed publications, to critically evaluate the effectiveness of several viral indicators of wastewater pollution, including common enteric viruses (mastadenoviruses, polyomaviruses, and Aichi viruses), the pepper mild mottle virus (PMMoV), and gut-associated bacteriophages (Type II/III FRNA phages and phages infecting human Bacteroides species, including crAssphage). Our analysis suggests that overall, human mastadenoviruses have the greatest potential to indicate contamination by domestic wastewater due to their easy detection, culturability, and high prevalence in wastewater and in the polluted environment. Aichi virus, crAssphage and PMMoV are also widely detected in wastewater and in the environment, and may be used as molecular markers for human-derived contamination. We conclude that viral indicators are suitable for the long-term monitoring of viral contamination in freshwater and marine environments and that these should be implemented within monitoring programmes to provide a holistic assessment of microbiological water quality and wastewater-based epidemiology, improve current risk management strategies and protect global human health. [Display omitted] •Human mastadenoviruses are robust indicators for human-associated pollution in water.•Bacteroides-associated phages and crAssphage are promising indicators.•Multiple indicators should be used to assess wastewater treatment efficiency.•Survival and abundance of indicator viruses should be further assessed.